Joint Bayesian estimation of quasar continua and the Lyα forest flux probability distribution function - Eilers, Anna-Christina; Hennawi, Joseph F.; Lee, Khee-Gan (The astrophysical journal, 2017)
We present a new Bayesian algorithm making use of Markov Chain Monte Carlo sampling that allows us to simultaneously estimate the unknown continuum level of each quasar in an ensemble of high-resolution spectra, as well as their common probability distribution function (PDF) for the transmitted Ly α forest flux. This fully automated PDF regulated continuum fitting method models the unknown quasar continuum with a linear principal component analysis (PCA) basis, with the PCA coefficients treated as nuisance parameters. The method allows one to estimate parameters governing the thermal state of the intergalactic medium (IGM), such as the slope of the temperature-density relation ##IMG## [http://ej.iop.org/images/0004-637X/844/2/136/apjaa7e31ieqn1.gif] $γ -1$ , while marginalizing out continuum uncertainties in a fully Bayesian way. Using realistic mock quasar spectra created from a simplified semi-numerical model of the IGM, we show that this method recovers the underlying quasar continua to a precision of ##IMG## [http://ej.iop.org/images/0004-637X/844/2/136/apjaa7e31ieqn2.gif] $\simeq 7 % $ and ##IMG## [http://ej.iop.org/images/0004-637X/844/2/136/apjaa7e31ieqn3.gif] $\simeq 10 % $ at z = 3 and z = 5, respectively. Given the number of principal component spectra, this is comparable to the underlying accuracy of the PCA model itself. Most importantly, we show that we can achieve a nearly unbiased estimate of the slope ##IMG## [http://ej.iop.org/images/0004-637X/844/2/136/apjaa7e31ieqn4.gif] $γ -1$ of the IGM temperature-density relation with a precision of ##IMG## [http://ej.iop.org/images/0004-637X/844/2/136/apjaa7e31ieqn5.gif] $± 8.6 % $ at z = 3 and ##IMG## [http://ej.iop.org/images/0004-637X/844/2/136/apjaa7e31ieqn6.gif] $± 6.1 % $ at z = 5, for an ensemble of ten mock high-resolution quasar spectra. Applying this method to real quasar spectra and comparing to a more realistic IGM model from hydrodynamical simulations would enable precise measurements of the thermal and cosmological parameters governing the IGM, albeit with somewhat larger uncertainties, given the increased flexibility of the model.
Gesehen am 29.11.2018